Concepts of Egr-1 Activation - A Hub for Signal Transduction Cascades - Pagel, Judith-Irina; Deindl, Elisabeth (Current Signal Transduction Therapy, 2010)
The early growth response-1 (Egr-1) gene encodes a Cys2-His2-type zinc-finger transcription factor. A broad range of extra cellular stimuli are known to lead to its induction thus furthering growth, proliferation, differentiation or apoptosis. Accordingly, Egr-1 is involved in a variety of diseases such as atherosclerosis or cancer. Among other functional elements, five serum response elements (SRE) have been identified in the promoter region of Egr-1. The Rho/Rho-kinase pathway has been shown to regulate actin reorganization via LIM-kinase mediated cofilin phosphorylation. Recent studies revealed the actin binding striated muscle activator of Rho signaling (STARS) to promote translocation of myosin related transcription factors (MRTFs) into the nucleus leading to serum response factor (SRF) activation. The ternary complex factor (TCF) Elk-1 eventually bridges the gap between SRF mediated gene transcription and the Raf/MEK/ERK pathway. Furthermore, the Egr-1 promoter has two cAMP response elements (CREs), whose relevance for gene expression is still controversial. An Egr-1 binding site (EBS) is located on the Egr-1 promoter itself arguing for a negative feedback mechanism. The acquired knowledge on transcriptional regulation, however, is not entirely understood. In this review we highlight upstream and downstream signaling in vitro and in vivo associated with Egr-1.
Keywords: Egr-1